Pengaruh Fasilitas Sekolah terhadap Hasil Belajar Siswa di SD Negeri 32 Kota Bengkulu - Yola Septia Utami; Aziza Aryati; Abdul Aziz Mustamin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to determine the effect of school facilities on student learning outcomes at SDN 32 Bengkulu City. This research uses a quantitative approach, data collection techniques using questionnaires, documentation and observation methods. The method used is ex post facto. In this research, the subjects or informants were class II students and class II teachers at SDN 32 Bengkulu City. Sampling was carried out using the Simple Random Sampling technique with a total of 49 students. The observations in this research were all students at SDN 32 Bengkulu City. Based on data analysis, it can be concluded that there is an influence of school facilities on student learning outcomes at SDN 32 Bengkulu City. This can be seen from the results of the t test analysis with a constant value of 71.983, which means that if the school facilities have a value of 0, then the learning outcomes (Y) have a positive value of 71.983%. The regression coefficient for the school facilities variable (X) is 0.131, which means that if school facilities are improved by 1%, learning outcomes (Y) will increase by 0.131%. The coefficient is positive between school facilities and student learning outcomes. The better the school facilities, the more student learning outcomes will increase. So, there is an influence of school facilities on student learning outcomes with 53.1% results in the good category.” Keywords: learning outcomes, School facilities,